APPLICATION OF DIRECT LEARNING MODELS TO IMPROVE THE ABILITY TOPLAYING PIANICA MUSIC IN ELEMENTARY SCHOOL - Annisa Fitri Bestari (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This research is motivated by the low ability of children to play the pianica instrument in grade V students of 012 Lubuk Terentang. This research is a classroom action research aimed at improving children’s ability in playing the pianica musical instrument by applying a direct learning model. The subjects of this research were eight grade V students of SDN 012 Lubuk Terentang. The instruments for data collection in this study were teacher activity sheets, student activity sheets, and student ability assessment sheets in playing the pianica musical instrument. This study presents preliminary data before applying the direct learning model, obtaining a base score of 40.62, which increased to 53.36 in cycle I. In cycle II, the ability increased to 64.82, and in cycle III it increased to 81.17. Teacher activity in cycle I at the first meeting obtained a percentage of 35% (less category), at the second meeting increased to 40% (less category), and at the third meeting reached 50% (less category). In cycle II at the first meeting, teacher activity reached 70% (enough category), at the second meeting 75% (good category), and at the third meeting 80% (good category). In cycle III at the first meeting teacher activity increased to 85% (good category), at the second meeting 90% (excellent category), and at the third meeting 95% (excellent category). The results of this study show that students begin to understand the pianica musical instrument material after applying the direct learning model, marked by an increase in teacher and student activities in each cycle. The results of research in grade V SDN 012 Lubuk Terentang prove that the application of the direct learning model can improve children’s ability to play the pianica instrument in grade V students of SDN 012 Lubuk Terentang Kecamatan Gunung Toar Kabupaten Kuantan Singingi.